The invisible enemy : a natural history of viruses - Crawford, Dorothy H. (Oxford ; New York : Oxford University Press, 2009)
In 1969 the US Surgeon General confidently declared, "We can now close the book on infectious diseases." The advent of AIDS has proven him spectacularly wrong, and in recent years the world has witnessed infectious outbreaks of other highly lethal viruses such as Hanta, Ebola, and Lassa fever. Flu strains are getting stronger and stronger each year. But what, exactly, is a virus? How does it work? And what is the best way to fight it? In Invisible Enemy, Dorothy Crawford offers clear answers to these and many other questions. She shows precisely how viruses, with their amazing ability to mutate, have caused devastating diseases in the past, and continue to pose one of the greatest challenges to science. A virus is disarmingly small and simple--a minute piece of genetic material wrapped in a protein coat. And yet it can cause major chaos. Smallpox killed over 300 million people in the twentieth century before it was eradicated in 1980; at that time, measles still killed two and half million children a year; and the HIV virus is now the leading cause of death in Africa. Crawford lucidly explains all aspects of these deadly parasites and discusses controversial subjects such as CFS and Gulf War Syndrome. She goes on to consider how we've coped with viruses in the past, where new viruses come from, and whether a new virus could wipe out the human race. For anyone seeking a deeper understanding of these remarkably efficient killers, Invisible Enemy provides a compelling account of their history, their effects on us, and their possible future -- publisher's note.
"First published 2000".
Includes bibliographical references (p. [235]-249) and index.
Keywords: Viruses -- Popular works; Medical virology -- Popular works; Viruses -- Ecology